Cunceviciana in Polish Monastic, Private, and Public Libraries of the 18th and 19th Centuries - Tkachuk, Olga (Lietuvos istorijos studijos, 2025)
The study examines the prevalence of copies of Cunceviciana2 in Polish libraries of the 18th and 19th centuries, with a focus on books currently held in the collection of early printed books at the Ossoliński National Institute in Wrocław. Individual copies of publications associated with Josaphat Kuntsevych from other Polish and Ukrainian book collections were also used for provenance analysis. The research is limited to works printed in Latin script prior to the 19th century. The collected data serve to illuminate the historical dissemination of Cunceviciana and to elucidate the factors contributing to their noteworthiness in both ecclesiastical and lay contexts within Poland over the aforementioned centuries.